The Effect of Murottal Al-Qur’an Audio Therapy on the Anxiety Levels of Cito Hemodialysis Patients - Nikmatul Mazidah; Suhari Suhari; Widya Addiarto (Health and Technology Journal (HTechJ), 2025)
Patients undergoing emergency hemodialysis therapy will experience anxiety caused by financial crises, fear of death, and stressors. One of the effective distraction techniques used to overcome anxiety in patients is using Murottal Al-Qur'an Audio. The brain will release neuropeptides that can provide comfort and pleasure when stimulated by Murottal Al-Qur'an Audio, which will lessen the patient’s anxiety. The research design used is quantitative research with a pre-experimental One-Group Pretest-Posttest Design approach. The population in this study were patients undergoing Cito hemodialysis who met the inclusion criteria, with a sample of 31 respondents. The sampling technique used accidental sampling. The research results were obtained before Murottal Al-Qur’an Audio was carried out from a total of 31 respondents: 18 (58.1%) respondents experienced severe anxiety, 12 (38.7%) respondents experienced moderate anxiety, and 1 (3.2%) respondent experienced mild anxiety. After carrying out Murottal Al-Qur'an Audio, it was found that 21 (67.7%) respondents experienced mild anxiety, 10 (32.3%) respondents experienced moderate anxiety, and none (0%) respondents experienced severe anxiety. After analysis using the Wilcoxon Signed Ranks Test, the results showed p-value = 0.000, indicating Murottal Al-Qur'an Audio's influence on the Anxiety Level of Cito Hemodialysis Patients. It is hoped that hospital management can use Audio Murottal Al-Qur'an as a non-pharmacological technique/alternative therapy in providing nursing care to reduce the level of anxiety in patients undergoing Cito hemodialysis.